Mode of delivery of obese fetuses: A dilemma hardening the decision-making. (March 2019) - Beksac, M. Sinan; Orgul, Gokcen; Katlan, Doruk Cevdi
Abstract: We aimed to review the delivery mode of overweight fetuses (>4000 g). We retrospectively evaluated 11418 deliveries in our hospital, and found 573 overweight neonates with a rate of 5%. The total cesarean section (CS) rate was 72.1% for overweight fetuses; whereas overall total CS rate was 52.9% at the same period. The stillbirth rate was 1.1% in the overweight fetuses. The birthweights of 511 (89.2%) subjects were between 4000 and 4499 g, whereas the birthweights of 55 (9.6%) and 7 (1.2%) overweight neonates were between 4500 and 4999 and ≥ 5000 g, respectively. Carbohydrate metabolism disorders in pregnancy were recorded only in 107 cases (18.67%). Prenatally suspected overweight fetuses (>4000 g) seem to concern obstetricians while decision-making about the delivery mode, which is why a high CS rate was recorded for overweight fetuses.